Digitalization Possible – Main Achievements in Bulgarian Libraries - Popova, Elena; Todorova, Tania (Bobcatsss, 2023)
The aim of the paper is to systematize the main achievements regarding the digitalization of the cultural heritage in Bulgaria and to highlight the problems and recommendations for the continued integration of the Bulgarian cultural heritage in the pan-European context. The study is focused on six projects, split into two categories – initiated by Bulgarian institutions and participation in global initiatives. The idea is to show the overall progress in the development of Bulgarian libraries, and not to compare the importance of different projects. It is time to show some good examples and practices, which strengthened the place of Bulgarian specialists on the European and world stage: Projects BG0046 “Digitization and preservation of the written heritage of Bulgaria” and “Manuscripts and documentary monuments from the Bulgarian lands XIII – XVIII c.”; Project “Varna Digital Library”; Project “Digital cultural and historical heritage of The Municipality of Plovdiv”; IMPACT project; TELPlus project. The results achieved in these projects are an important example of progress in the perception of digitalization as a key method for preserving cultural heritage. The specificity of this process in the modern information society requires reconsideration of some important issues regarding copyright and preparation of well informed specialists. This is why the report also presents a short description of the аcademic discipline “Digitalization and Copyright” in University of Library Studies and Information Technologies (ULSIT) in order to show how important it is to integrate knowledge about the problems and achievements of the modern information society in the educational system.